2014
DOI: 10.5435/jaaos-22-07-420
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Ossification of the Posterior Longitudinal Ligament in the Cervical Spine

Abstract: Although classically associated with patients of East Asian origin, ossification of the posterior longitudinal ligament (OPLL) may cause myelopathy in patients of any ethnic origin. Degeneration of the PLL is followed by endochondral ossification, resulting in spinal cord compression. Specific genetic polymorphisms and medical comorbidities have been implicated in the development of OPLL. Patients should be evaluated with a full history and neurologic examination, along with cervical radiographs. Advanced imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 28 publications
0
69
0
1
Order By: Relevance
“…9,12 However, for anterior surgery in patients with OPLL, it has been reported that this approach is technically demanding and associated with a higher incidence of operation-related complications. 1,9 These complications included the risk of a dural tear or CSF leakage, which was difficult to repair in anterior cervical surgery. 2,13 The incidence of dural tear and CSF leakage has been reported to be 13.7-fold greater in patients with OPLL compared with patients affected by other conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12 However, for anterior surgery in patients with OPLL, it has been reported that this approach is technically demanding and associated with a higher incidence of operation-related complications. 1,9 These complications included the risk of a dural tear or CSF leakage, which was difficult to repair in anterior cervical surgery. 2,13 The incidence of dural tear and CSF leakage has been reported to be 13.7-fold greater in patients with OPLL compared with patients affected by other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Although the selection of an anterior or posterior approach has been the subject of debate, multilevel cord compression by OPLL and preoperative lordotic sagittal alignment are conditions that favor a posterior approach. 11 However, many studies have shown that poor clinical and radiological outcomes may occur if posterior laminoplasty or laminectomy is performed in patients with cervical kyphosis.…”
Section: Discussionmentioning
confidence: 99%
“…As spinal cord compromise is caused by various lesions in DCM, compression may occur anteriorly (disc, osteophyte, or OPLL), posteriorly (hypertrophy or ossification of ligamentum flavum), and the concept of decompression performed from the side of major compressive factors seems to be straightforward and well accepted. For example, it may be that superior outcomes result from anterior decompression for OPLL with more than 60 % of canal occupying ratio [9][10][11][12]. However, DCM can frequently be associated with multiple degenerative lesions and compression can be circumferential.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Laminoplasty (LMP) is a widely accepted surgical procedure for ossification of the posterior longitudinal ligament (OPLL) of the cervical spine [1][2][3][4]. Thickening of OPLL can occur in the long term after LMP, possibly resulting in recurrence of spinal cord compression and deterioration of neurological symptoms [5,6].…”
Section: Introductionmentioning
confidence: 99%